Corrosion resistance of nickel-containing alloys in sulphuric acid and related compounds (CEB-1). (Practical guide to the use of nickel-containing alloys, 2020)
Data present in this booklet on sulfuric acid are gathered from a variety of sources, including laboratory and field exposures as well as the literature, technical bulletins of the alloy producers and actual plant experience.